Pedagogical Managerial Mechanisms of the Labor Market Needs in a New Generation of Specialists - Skorobogatova, Anna I.; Khanmurzina, Rimma R.; Tararina, Larisa I.; Mirzagitova, Alsu L.; Yakushevskiy, Maksim V.; Sokolova, Ekaterina I.; Faizrakhmanova, Aigul L.; Gainullina, Rezeda R. (International Review of Management and Marketing, 2016)
Supply and demand are implemented in the competition between workers for engaging in a particular workplace or work performing, as well as among employers to attract the necessary labor force as a commodity, possessing intelligence, competence, qualification. Under these circumstances, a graduate of an educational institution is not in a favorable position for himself, because he does not have the expected by the customers, practical experience. The paper is aimed at scientific justification of pedagogical mechanisms of management of labor market needs in specialists of a new generation. The leading method in the study of this problem is the comparative method identifying pedagogical mechanisms of supply and demand management in specialists of the new generation in the labor market. The paper presents the results of significant increase fixing in the number of youth unemployment that requires the use of preventive and corrective measures in the management of the needs of the labor market. The authors revealed the structure and content of an innovative model of educational institutes' specialist graduates, including the structure of the individual; personal qualities; managerial roles; formulation of objectives; analysis, examination; the integration of new management ideas; the use of modern information and others. Presented in the article model of training of a competent professional, expected by labor market, also includes the curriculum (list of subjects, number of hours), requirements for the competence of each academic subject, and indicators and criteria of training quality, the detailed content of the curricula, scientific - methodical maintenance of educational process. Keywords: Labor Market Needs, Demand for Professionals, Management, Mechanisms. JEL Classifications: I21, I23, Z13